2009
DOI: 10.1016/j.trstmh.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia, folate and vitamin B12 deficiency among pregnant women in an area of unstable malaria transmission in eastern Sudan

Abstract: A cross-sectional study was carried out between October 2007 and January 2008 to investigate the prevalence and types of anaemia among pregnant women of eastern Sudan. Socio-demographic and obstetrical data were collected using a questionnaire. Haemoglobin (Hb), serum ferritin, serum folate and vitamin B(12) were assessed using standard laboratory methods. Two hundred and seventy-nine pregnant Sudanese women were recruited. Anaemia (Hb <11 gdl) and iron deficiency (ferritin <15 microg/l) were prevalent in 80.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 15 publications
0
29
4
Order By: Relevance
“…The prevalence of anaemia in this study was lower than the prevalence (70-80%) that we recently reported among pregnant women and among adolescent girls (96.8%) of eastern Sudan [3,14,15]. The lower prevalence of anaemia in the current study could be explained by the differences in the seasons during which the surveys were conducted.…”
Section: Discussioncontrasting
confidence: 90%
“…The prevalence of anaemia in this study was lower than the prevalence (70-80%) that we recently reported among pregnant women and among adolescent girls (96.8%) of eastern Sudan [3,14,15]. The lower prevalence of anaemia in the current study could be explained by the differences in the seasons during which the surveys were conducted.…”
Section: Discussioncontrasting
confidence: 90%
“…An additional striking finding was the pooled insufficiency rate of 65% (I 2 = 95%) ( Figure 4) (28,52,65,77,93) from the 5 studies in the Eastern Mediterranean region. On the contrary, insufficiency rates of ,8% were found in 2 studies conducted in Thailand and Sudan, where the authors attributed the low rates of insufficiency to the consumption of fish and animal/fermented products, respectively (although details of dietary intake were not provided) (49,50).…”
Section: Prevalence Of Vitamin B-12 Insufficiency In Pregnancymentioning
confidence: 99%
“…The prevalence of anemia in lactating and pregnant women was 43% (95% CI, 41%-45%) and 84% of anemia was iron deficiency anemia followed by normocytic normocromic anemia This finding is lower when compared to findings from eastern Ethiopia [48] Germany [32], Nepal [33], India [35], eastern Sudan [40], Kenya [41]; agrees with findings from Ghana [39]and higher than finding from northern Ethiopia [49] southern Ethiopia [45] Trinidad and Tobago [34], Benin [42]. These might be due to the reason that different distribution of determinants of anemia across different social, cultural or geographical areas.…”
Section: Discussionmentioning
confidence: 97%